Effect of Immersion Time on CA/NMP Membrane Preparation for Microplastic Separation in Water - Rahmah, Annisa Alifia; Rifai, Muhammad Ayub; Nurkhamidah, Siti; Rahmawati, Yeni (Eksergi, 2024)
Indonesia produces more than 4.8 million tons of plastic waste every year, but it has not been managed properly so that it will end up in Indonesian waters. This plastic waste is then decomposed into microplastics (MPs) which are <5 mm in size. The presence of MPs in Indonesian waters can have a negative impact on living things, so it needs to be separated from the waters. One method that is considered to separate MPs in water is microfiltration using Membrane Technology. This study aims to determine the effect of immersion time on the characteristics and performance of microfiltration membranes. The fabrication of membrane was prepared using phase inversion method, with Cellulose Acetate (CA)/N-Methyl-2Pyrrolidone (NMP) as polymer/solvent and distilled water as non-solvent. Characteristics analysis to determine the hydrophilicity of the membrane such as contact angle, moisture content, porosity and pore size of the membrane. Scanning Electrone Microscope (SEM) to determine the surface morphology and structure of the membrane, and analysis of microplastic rejection in water. The results of the characteristic analysis showed that the membrane was hydrophilic with a contact angle in the range of 61-53°, porosity of 80-83%, moisture content of 79-82% and pore size of 8.4-5.8 μm in accordance with the microfiltration membrane, as well as the membrane rejection ability reached 99%. So that membrane technology needs to be developed again to separate MPs in water.